Correlation between blood pressure changes and AMS, sleeping quality and exercise upon high-altitude exposure in young Chinese men - Liu, Yang; Zhang, Ji-Hang; Gao, Xu-Bin; Wu, Xiao-Jing; Yu, Jie; Chen, Jian-Fei; Bian, Shi-Zhu; Ding, Xiao-Han; Huang, Lan (Military Medical Research, 2014)
Background: Excessive elevation of arterial blood pressure(BP) at high altitude can be detrimental to our health due to acute mountain sickness(AMS) or some AMS symptoms. This prospective and observational study aimed to elucidate blood pressure changes induced by exposure to high-altitude hypoxia and the relationships of these changes with AMS prevalence, AMS severity, sleep quality and exercise condition in healthy young men.Methods: A prospective observational study was performed in 931 male young adults exposed to high altitude at 3,700 m(Lhasa) from low altitude(LA, 500 m). Blood pressure measurement and AMS symptom questionnaires were performed at LA and on day 1, 3, 5, and 7 of exposure to high altitude. Lake Louise criteria were used to diagnose AMS. Likewise, the Athens Insomnia Scale(AIS) and the Epworth Sleepiness Scale(ESS) were filled out at LA and on day 1, 3, and 7 of exposure to high altitude.Results: After acute exposure to 3,700 m, diastolic blood pressure(DBP) and mean arterial blood pressure(MABP) rose gradually and continually(P<0.05). Analysis showed a relationship with AMS for only MABP(P<0.05) but not for SBP and DBP(P>0.05). Poor sleeping quality was generally associated with higher SBP or DBP at high altitude, although inconsistent results were obtained at different time(P<0.05). SBP and Pulse BP increased noticeably after high-altitude exercise(P<0.05).Conclusions: Our data demonstrate notable blood pressure changes under exposure to different high-altitude conditions: 1) BP increased over time. 2) Higher BP generally accompanied poor sleeping quality and higher incidence of AMS. 3) SBP and Pulse BP were higher after high-altitude exercise. Therefore, we should put more effort into monitoring BP after exposure to high altitude in order to guard against excessive increases in BP.